Exploring high school teachers experiences in teaching Life Orientation Education in rural South Africa - Mulaudzi , Shumani; Hoque, Muhammad (Orapuh Journal, 2025)
Introduction Life Orientation (LO) education aims to promote social justice, human rights, and holistic learner development. However, implementation challenges in rural South African schools undermine its effectiveness. Purpose This study explores the challenges and opportunities associated with LO education implementation in Limpopo Province, South Africa. Methods A qualitative approach was employed, utilizing semi-structured interviews with 16 purposively selected LO educators. Data were analyzed thematically. Results The findings reveal that while teachers acknowledge the significance of LO, learners often perceive it as non-essential. Key challenges include inadequate teacher training, rigid learner attitudes, and resource constraints. Conclusion The study underscores the urgency of policy interventions that provide clear guidance, enhanced training, and increased funding to support LO instruction in rural schools.